2020
DOI: 10.18632/aging.103626
|View full text |Cite
|
Sign up to set email alerts
|

A novel hypoxic tumor microenvironment signature for predicting the survival, progression, immune responsiveness and chemoresistance of glioblastoma: a multi-omic study

Abstract: The hypoxic tumor microenvironment (TME) was reported to promote the aggressive phenotype, progression, recurrence, and chemoresistance of glioblastoma (GBM). We developed and validated a hypoxia gene signature for individualized prognostic prediction in GBM patients. In total, 259 GBM-specific hypoxia-related genes (HRGs) were obtained in hypoxic cultured GBM cells compared with normoxic cells. By applying the k-means algorithm, TCGA GBM patients were divided into two subgroups, and the patients in Cluster 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Principal component analysis displayed that there were significant differences among the three different clusters (Figure 1C). What's more, the heat map showed that the expression of differential genes between different clusters was significantly different, which proved the reliability and stability of the three clusters (Figure 1D) (11).…”
Section: Cluster Analysis Of Five Geo Data Sets Based On Hrgsmentioning
confidence: 77%
“…Principal component analysis displayed that there were significant differences among the three different clusters (Figure 1C). What's more, the heat map showed that the expression of differential genes between different clusters was significantly different, which proved the reliability and stability of the three clusters (Figure 1D) (11).…”
Section: Cluster Analysis Of Five Geo Data Sets Based On Hrgsmentioning
confidence: 77%
“…Hypoxia-associated genes (such as HIFs, ARD1A, FIH) and their target gene products are known to be hyperactivated in tumor, which involved in different tumoral mechanisms of cancer. Previous studies have addressed the vital roles hypoxia status plays in the failure of conventional cancer therapies and poor prognosis of multiple cancer such as liver cancer ( Bao and Wong, 2021 ), bladder cancer ( Zhang et al, 2021 ), glioblastoma ( Wang et al, 2020 ) and breast cancer ( McAleese et al, 2021 ). Therefore, Hypoxia-associated genes can be widely used as promising prognostic predictors and therapeutic targets for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have addressed the vital roles of hypoxia status playing in the failure of conventional cancer therapies and poor prognosis of multiple cancer (15,16). Due to the significant roles of hypoxia, the hypoxia-related gene signatures of glioblastoma (12), colorectal cancer (17), hepatocellular carcinoma (18), bladder cancer (19), renal cell carcinoma (20), and breast cancer (21)(22)(23)(24) have been constructed to predict patient survival outcomes. As the most malignant and aggressive breast tumor, TNBC is characterized by severely low tumor oxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…As reported by Wang et al. ( 12 ), a total of 1,694 genes in 65 gene sets were selected as HRGs with the following keywords: hypoxia AND Homo sapiens ( Supplementary Table S1 ). All the known HRGs were screened from GO, KEGG, and Reactome databases by using the Molecular Signatures Database (MSigDB), a collection of annotated gene sets.…”
Section: Methodsmentioning
confidence: 99%